MANULANGI: JEJAK SPIRITUAL DALAM TRADISI BATAK YANG MENGINSPIRASI PEMBINAAN IMAN INTERGENERASI - Junjungan Simorangkir; Johanes Waldes Hasugian; Bintahan Marodjahan; Shindy Roidola Napitupulu; Robert Juni Tua Sitio; Candra Tandi Reinhard Siagian (Sekolah Tinggi Teologi Arastamar Bengkulu, 2026)
The Manulangi tradition in Batak society is a cultural practice that represents children's respect for their parents while strengthening family solidarity. The values ​​in this tradition align with Christian teachings, particularly the command to honor parents (Exodus 20:12). However, most previous studies have emphasized the symbolic and socio-cultural aspects of the Manulangi tradition, resulting in little exploration of its pedagogical potential in Christian faith education. This study aims to reinterpret the Manulangi tradition as a pedagogical medium for intergenerational Christian faith education. The study used a descriptive qualitative method through observation and in-depth interviews with religious leaders, traditional leaders, and village heads in Lumban Suhi-Suhi Village, Pangururan District, Samosir Regency, North Sumatra. Data analysis was conducted through data reduction, thematic categorization, and theological-pedagogical analysis with source triangulation validation. The results show that Manulangi functions not only as a traditional tradition but also as a learning space for faith values ​​that enable the transfer of values ​​between generations, such as respect, love, responsibility, and family reconciliation. With a contextual theological approach and adult education, this tradition has the potential to be developed as a pedagogical medium in contextual Christian faith education for the Batak people.